1997
DOI: 10.1172/jci119127
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of human keratin 18 in association with cryptogenic cirrhosis.

Abstract: Mutations in 11 of the more than 20 keratin intermediate filaments cause several epidermal and oral associated diseases. No disease-associated mutations have been described in keratin 8 or 18 (K8/18) which are the major keratin pair in simple-type epithelia, as found in the liver, pancreas, and intestine. However, transgenic mice that express mutant keratin 18 develop chronic hepatitis, and have an increased susceptibility to drug-induced hepatotoxicity. Also, ectopic expression of epidermal K14 in mouse liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 33 publications
0
72
0
1
Order By: Relevance
“…38,39 It has been recently demonstrated that CK-18 mutations predispose their carriers to develop cryptogenic and noncryptogenic forms of cirrhosis. 40,41 Moreover, CK-18 mutations are associated with increased sensibility toward CD95-induced hepatocyte apoptosis. 42 Both CD95 as well as CD95L have been shown to be up-regulated in chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 It has been recently demonstrated that CK-18 mutations predispose their carriers to develop cryptogenic and noncryptogenic forms of cirrhosis. 40,41 Moreover, CK-18 mutations are associated with increased sensibility toward CD95-induced hepatocyte apoptosis. 42 Both CD95 as well as CD95L have been shown to be up-regulated in chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…57 Structure and function of the cytokeratin IF cytoskeleton is not only affected by gene mutations but is also rapidly and reversibly modulated by posttranslational modifications, thus making the cytokeratin IF cytoskeleton a potential target for a variety of environmental factors. 41 Phosphorylation is one of the most important means of regulating protein function in response to extracellular stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,45 The most common causes, such as viral and autoimmune hepatitis, or alcoholic use of K8/18 as tumor markers involves staining of tissue liver disease. 39 The low frequency of the identified K18 mutafrom tumor specimens to clarify their cell origin. 42,43 Measuretion makes it unlikely to be a polymorphism, but, more imporment of the serum component ''tissue polypeptide antigen,'' tantly, the mutation was associated with a filament-assembly which consists of K8/18/19, 46 in cancer patients' serum has defect if introduced into a recombinant K18 protein and anabeen tested as a hepatoma tumor marker but did not compare lyzed in vitro.…”
Section: Disease Association With If Proteinsmentioning
confidence: 99%
“…42,43 Measuretion makes it unlikely to be a polymorphism, but, more imporment of the serum component ''tissue polypeptide antigen,'' tantly, the mutation was associated with a filament-assembly which consists of K8/18/19, 46 in cancer patients' serum has defect if introduced into a recombinant K18 protein and anabeen tested as a hepatoma tumor marker but did not compare lyzed in vitro. 39 Although familial idiopathic cases of liver in specificity to a-fetoprotein. 47 With regard to the patients disease are unusual, 40 the involvement of K8/18 mutations with autoimmune hepatitis who develop antibodies to soluble in liver disease is attractive on several fronts.…”
Section: Disease Association With If Proteinsmentioning
confidence: 99%
See 1 more Smart Citation